2020
DOI: 10.3389/fneur.2020.00822
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Analysis of Lesion-Symptom Relationships in Acute Vestibular and Ocular Motor Stroke

Abstract: Background: Diagnosing stroke as a cause of acute vertigo, dizziness, or double vision remains a challenge, because symptom characteristics can be variable. The purpose of this study was to prospectively investigate lesion-symptom relationships in patients with acute vestibular or ocular motor stroke. Methods: Three hundred and fifty one patients with acute and isolated vestibular or ocular motor symptoms of unclear etiology were enrolled in the EMVERT lesion trial. Symptom quality was assessed by the chief co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
2
7
0
10
Order By: Relevance
“…Second, vertigo, imbalance itself as a disabling symptom may be less significant, as vestibular tone imbalance due to central lesions are known to resolve within 2–4 weeks as a compensatory process ( 43 ). The cerebellum takes role in this compensatory mechanism within weeks, unless the patients have lesions in specific regions within the cerebellar hemispheres which might hinder compensatory processes ( 44 , 45 ). However, care should be noted in interpretation of the current findings because previous studies have found non-lacunar mechanisms in half of stroke patients presenting with AVS ( 46 ), and heterogenous stroke etiologies are also seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, vertigo, imbalance itself as a disabling symptom may be less significant, as vestibular tone imbalance due to central lesions are known to resolve within 2–4 weeks as a compensatory process ( 43 ). The cerebellum takes role in this compensatory mechanism within weeks, unless the patients have lesions in specific regions within the cerebellar hemispheres which might hinder compensatory processes ( 44 , 45 ). However, care should be noted in interpretation of the current findings because previous studies have found non-lacunar mechanisms in half of stroke patients presenting with AVS ( 46 ), and heterogenous stroke etiologies are also seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Die häufigsten episodischen Schwindelsyndrome sind der gutartiger Lagerungsschwindel, der meist den posterioren Bogengang betrifft (3), der Morbus Menière, der morphologisch durch einen Endolymphhydrops gekennzeichnet ist (4), und die vestibuläre Migräne, bei der funktionelle pathologische Veränderungen in zerebellären und thalamischen vestibulären Netzwerken nachgewiesen wurden (5). Chronische Schwindelsyndrome betreffen entweder bilaterale vestibuläre Afferenzen (bilaterale Vestibulopathie) (6), kortikale sensorimotorische Netzwerke (funktioneller Schwindel) ( 7) oder (vestibulo-)zerebelläre Strukturen (8).…”
Section: Akute Schwindelsyndromeunclassified
“…Hingegen sind Fragen nach der Symptomqualität (Dreh-versus Schwankschwindel), Symptomdauer (Stunden bis Tage) und Symptomintensität (milde versus starke Schwindelbeschwerden) weniger hilfreich. Eine prospektive Erhebung der Schwindelqualität bei Patienten mit vestibulären und okulomotorischen Schlaganfällen zeigte, dass 43% der Patienten über Schwankschwindel, 40% über Drehschwindel und 17% über Doppelbilder klagten [8]. Vor allem bei Läsionen im Kleinhirn waren Dreh-oder Schwankschwindel als Leitsymptom fast gleich häufig.…”
Section: Akute Schwindelsyndromeunclassified
See 1 more Smart Citation
“…It has been established that stroke accounts for 2-13.4% of patients presenting to the emergency department (ED) with dizziness (1)(2)(3)(4)(5). Stroke is the second leading cause of death globally and has a limited treatment time window (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%